MSK direct sequence spread spectrum system incorporating SAW tapped delay line and SAW shaping filter - Zenzinger, Alesander; Mathiae, S.; Russer, Peter; Reindl, Leonhard; Weigel, Robert (Proceedings of IEEE Ultrasonics Symposium, 1997)
The present work deals with the IF section of an indoor wireless TDMA/CDMA (TCDMA) communication system operating in the 2.45 GHz ISM band. Spreading and despreading is done at the 361 MHz IF with an extremely wide bandwidth of 65 MHz which is greater than the coherence bandwidth of the UHF indoor radio channel. For the modulation of the data we employ on off keying (OOK), and for the spreading minimum shift keying (MSK). Two types of MSK modulators have been developed, one with a SAW tapped delay line (TDL) and one with a SAW shaping filter. Despreading is done by another SAW TDL, which operates as a matched filter
elib2cris::1512001600,zenzinger1997b